Pengembangan bahan ajar modul terintegrasi problem based learning pada materi laju reaksi - Simorangkir, Risdayati; Sinaga, Marudut (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research aims to (1) analyze chemistry teaching materials on reaction rates used in schools according to BSNP standards; (2) describe the feasibility of integrated problem-based learning module teaching materials on reaction rate material based on BSNP criteria; and (3) know student learning outcomes after being given teaching materials for the integrated problem-based learning module on reaction rate material. This research uses the R&D method with the ADDIE model, which includes stages (analysis, design, development, implementation, and evaluation). The product developed was validated by four expert validators, consisting of two chemistry lecturers and two chemistry teachers. From the research results, it was found that the analyzed teaching materials were suitable in terms of content, presentation, contextual, graphic, and language, in accordance with the feasibility aspects of BSNP. Students show a high level of interest in the developed module based on the presentation assessment. Then, student learning outcomes using integrated problem-based learning module teaching materials on reaction rate material based on data processing are capable and effective in improving student learning outcomes.